Enhanced Recovery After Surgery Protocols for Head and Neck Cancer: Systematic Review and Meta‐analysis. (5th February 2023) - Kattar, Nrusheel; Wang, Steven X.; Trojan, Jeffrey D.; Ballard, Craig R.; McCoul, Edward D.; Moore, Brian A.
Abstract: Objective: Enhanced recovery after surgery (ERAS) protocols aim to optimize the pre‐, intra‐, and postoperative care of patients to improve surgery outcomes, reduce complications, decrease length of stay, and more. We aim to perform a systematic review and meta‐analysis of ERAS protocols for head and neck cancer surgery with or without microvascular reconstruction. Data Sources: PubMed, Embase, and Web of Science databases were queried, and abstracts were screened independently by 2 investigators. Review Methods: This review was conducted in accordance with the PRISMA guidelines. We included comparative observational studies but excluded animal studies, case reports, and case series. Results: Of 557 articles initially reviewed by title and/or abstract, we identified 30 for full‐text screening, and 9 met the criteria for qualitative synthesis. Meta‐analysis of length of stay revealed a mean decrease of 1.37 days (95% CI, 0.77‐1.96; I 2 = 0%; P < .00001) with the ERAS group as compared with non‐ERAS controls. The standardized mean difference of the morphine milligram equivalent was 0.72 lower (95% CI, 0.26‐1.18; I 2 = 82%; P = .002) in the ERAS group vs controls. The quality of studies was moderate with a median MINORS score of 18.5 (range, 13.5‐21.5). Conclusion: Implementation of ERAS protocols can lead to decreases in length of stay and opioid drug utilization. However, further high‐quality prospective studies of ERAS protocols are needed, especially with stratified analysis of outcomes based on the type of head and neck cancer surgery.